Enhanced cytotoxic and apoptotic potential in hepatic carcinoma cells of chitosan nanoparticles loaded with ginsenoside compound K. (15th October 2018) - Zhang, Jianmei; Wang, Yijun; Jiang, Yunyao; Liu, Tingwu; Luo, Yanyan; Diao, Enjie; Cao, Yufeng; Chen, Liang; Zhang, Liang; Gu, Qian; Zhou, Jinyi; Sun, Fengting; et al.
Graphical abstract: Highlights: CK-NPs were prepared as a delivery system using a self-assembly technique. CK-NPs had a size range of 170–200 nm which can accumulate in tumor site. CK-NPs could enhance the cytotoxic and apoptotic potentials. Abstract: Ginsenoside compound K (CK) has been shown to exhibit anticancer properties. In this study, chitosan nanoparticles loaded with ginsenoside compound K (CK-NPs) were prepared as a delivery system using a self-assembly technique with amphipathic deoxycholic acid-O carboxymethyl chitosan as the carrier, which improved the water solubility of CK. By evaluating drug loading, entrapment efficiency, and in vitro release behavior, the feasibility of CK-NPs as a drug carrier nanoparticle for the treatment of human hepatic carcinoma cells (HepG2) was investigated. Result revealed that CK and CK-NPs showed a dose-dependent inhibitory effect on HepG2 cells with IC50 values of 23.33 and 16.58 μg/mL, respectively. Furthermore, fluorescence imaging demonstrated that CK-NPs promoted cellular uptake in vitro . Therefore, all results indicated that CK-NPs might be a novel drug delivery system to improve the solubility and enhance the cytotoxic and apoptotic potentials of CK for effective liver cancer chemotherapy.